Analisis Hukum Mengenai Pertanggungjawaban Pidana Bagi Pembuat Aplikasi Game Online Yang Memuat Unsur Perjudian - Vania Sulistiano; Bambang Arwanto (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
The development of information and communication technology has had a significant impact on various aspects of life, including the emergence of new challenges in the form of online gambling crimes. One of the frequently highlighted applications is Higgs Domino Island, which uses chips as a transaction tool and contains gambling elements. This study aims to analyze criminal liability for the developers of online gaming applications that involve gambling elements based on positive law in Indonesia. The approach used in this research is a normative approach by examining regulations such as Articles 303 and 303 bis of the Criminal Code (KUHP) and Article 27 Paragraph (2) in conjunction with Article 45 Paragraph (2) of the Electronic Information and Transactions Law (UU ITE), which govern online gambling crimes. Additionally, administrative regulations such as Minister of Communication and Information Regulation No. 19 of 2014 allow the blocking of gambling applications or websites as a preventive measure. The research findings indicate that developers of applications containing gambling elements can be held criminally responsible in accordance with their role as organizers of electronic systems. This responsibility includes proving elements of fault, accountability, and intent to commit the crime. Criminal penalties of up to six years of imprisonment and/or fines up to one billion rupiah can be applied. This study emphasizes the importance of strict regulation and effective law enforcement to prevent the misuse of technology as a means of online gambling while also providing legal certainty for all parties involved.